The risk factors associated with post-transplantation BKPyV nephropathy and BKPyV DNAemia: a prospective study in kidney transplant recipients - Camilla Lorant; Justina Zigmantaviciute; Naima Ali; Ursa Bonnevier; Mattias Tejde; Bengt von Zur-Mühlen; Britt-Marie Eriksson; Anders Bergqvist; Gabriel Westman (BMC Infectious Diseases, 2024)
Abstract Background BK polyomavirus (BKPyV) infection after kidney transplantation can lead to serious complications such as BKPyV-associated nephropathy (BKPyVAN) and graft loss. The aim of this study was to investigate the incidence of BKPyVAN after implementing a BKPyV screening program, to map the distribution of BKPyV genotypes and subtypes in the Uppsala-Örebro region and to identify host and viral risk factors for clinically significant events. Methods This single-center prospective cohort study included kidney transplant patients aged ≥ 18 years at the Uppsala University Hospital in Sweden between 2016 and 2018. BKPyV DNA was analyzed in plasma and urine every 3 months until 18 months after transplantation. Also genotype and subtype were determined. A logistic regression model was used to analyze selected risk factors including recipient sex and age, AB0 incompatibility and rejection treatment prior to BKPyVAN or high-level BKPyV DNAemia. Results In total, 205 patients were included. Of these, 151 (73.7%) followed the screening protocol with 6 plasma samples, while184 (89.8%) were sampled at least 5 times. Ten (4.9%) patients developed biopsy confirmed BKPyVAN and 33 (16.1%) patients met criteria for high-level BKPyV DNAemia. Male sex (OR 2.85, p = 0.025) and age (OR 1.03 per year, p = 0.020) were identified as significant risk factors for developing BKPyVAN or high-level BKPyV DNAemia. BKPyVAN was associated with increased viral load at 3 months post transplantation (82,000 vs. < 400 copies/mL; p = 0.0029) and with transient, high-level DNAemia (n = 7 (27%); p < 0.0001). The most common genotypes were subtype Ib2 (n = 50 (65.8%)) and IVc2 (n = 20 (26.3%)). Conclusions Male sex and increasing age are related to an increased risk of BKPyVAN or high-level BKPyV DNAemia. BKPyVAN is associated with transient, high-level DNAemia but no differences related to viral genotype were detected.